The Effect of Labor Massage on Pain and Quality of Life of Pregnant Women - Nurul Aulia, Devy Lestari; Anjani, Arum Dwi Anjani; Putri, Dhini Triana; Tabriz, Nada; Aini, Rahma; Susanti, Alya (Raudhah Publisher, 2024)
This study aims to analyze the effect of labor massage on pain and quality of life of pregnant women. This study uses a quantitative design with a simple linear regression approach involving 100 maternity mothers as a sample. The results of the analysis showed that the variable of labor massage had a positive and significant influence on the pain of maternal quality of life, with a regression coefficient of 0.181 and a regression equation of Y = 17.473 + 0.181X. The results of hypothesis testing showed that the t-count value (2.065) was greater than the t-table (1.660) and the significance value of 0.042 was less than 0.05, which means that childbirth massage had a significant effect on the quality of life of pregnant women. The Gate Control Pain theory is used to explain that labor massage can activate the body's natural pain control mechanisms. These findings support the use of massage as one of the effective non-pharmacological methods to reduce pain and improve the mother's quality of life during childbirth. Based on these results, it is suggested that childbirth massage can be applied routinely as part of maternity care in health facilities.